Integration competence approach in estimation of the quality of training the students of the Ministry of Internal Affairs Higher Educational Establishment of Ukraine - Popov S.V (Kharkov National Pedagogical University, 2010)
Process of formings of skills of executing of acceptances of self-defense without the weapon and hand-to-hand chipping of cadets is construed. Mistakes are disclosed at practical application of acceptances. Motives of cadets to the profound training and self-improvement are indicated. It is established, that use of a professional - competent system of an estimation allows to receive the objective information on quality of formation of skills of self-defense without the weapon. It is indicated, that the summary surveillance should be realized on the basis of answers about activity on a solution of complex commitments of a professional context.